New Method of Design for Combined Tension and Bending - Aminmansour, Abbas (Engineering Journal, 2006)
A new method and aids for design of steel members subjected to combined tension and bending are presented based on the AISC Specification using the load and resistance factor design method. While the basic concepts utilized in this process apply to prismatic singly or doubly symmetric shapes subjected to flexure and axial tension, the focus of the discussions as well as the design aids developed in this paper apply to W-shapes only. The new design aids developed and presented in this paper offer the following advantages: - Save time in design. For example, compactness is already accounted for. - Can select more efficient sections with appropriate t, bx, and by coefficients depending on the relative magnitude of the applied axial force and bending moments. - Can choose from a wide range of sections. - Designer can easily judge the efficiency of a section by observing its values of t, bx, and by coefficients. - Tables provide means for easy calculation of (phi)tPn for a large number of sections.